Mixed Up? : That's Good for Motivation - Alexander K. Koch; Eloïc Peyrache (Institute for the Study of Labor (IZA), 2004)
An essential ingredient in models of career concerns is ex ante uncertainty about an agent's type. This paper shows how career concerns can arise even in the absence of any such ex ante uncertainty, if the unobservable actions that an agent takes influence his future productivity. By implementing effort in mixed strategies the principal can endogenously induce uncertainty about the agent's ex post productivity and generate reputational incentives. Our main result is that creating such ambiguity can be optimal for the principal, even though this exposes the agent to additional risk and reduces output. This finding demonstrates the importance of mixed strategies in contracting environments with imperfect commitment, which contrasts with standard agency models where implementing mixed strategy actions typically is not optimal if pure strategies are also implementable.
Keywords: M12; L14; J33; D80; 330; incentive contracts; reputation; mixed strategies; Anreizvertrag; Leistungsanreiz; Prestige; Karriereplanung; Asymmetrische Information; Agency Theory; Theorie